Pengembangan PENGEMBANGAN ODENG DARI SURIMI IKAN BULAN-BULAN (MEGALOPS CYPRINOIDES): EVALUASI SENSORI SERTA PERUBAHAN PH DAN KADAR AIR SELAMA PENYIMPANAN BEKU: Indonesia - Abdul Rahman; Siti Hajar (JURNAL LEMURU, 2026)
The Indo-Pacific Tarpon (Megalops cyprinoides Broussonet, 1782) is a common by-catch species that remains underutilized despite its high protein content (25,5g of protein/100g of fish). This study aims to innovate a frozen food product in the form of fish "odeng" (fish cake) to increase economic added value for the community. The research employed an experimental method focusing on three different formulations of surimi and tapioca starch: P1 (25%:75%), P2 (50%:50%), and P3 (75%:25%). Parameters tested included hedonic sensory analysis involving 30 untrained panelists based on SNI 2346:2015 standards, alongside moisture content and pH value analysis during 9 days of frozen storage at -18°C. The processing stages involved mixing surimi with salt, seasonings, and tapioca starch, followed by steaming the dough (±0,3cm) at 80°C to 100°C for 15 minutes, packaging, and freezing. The hedonic test results showed that P3 was the best formulation with an accumulative score of 7.9 (liked category), particularly excelling in flavor (8.2) and texture (8.5). During 9 days of storage, the moisture content of P1 dropped drastically to 16.83%, while P2 (45.38%) and P3 (62.40%) increased. The pH value of all formulations surged significantly from day 0 (average of 4.79) to day 1 (average of 6.23) and remained stable below 6.5 until day 9. This indicates that the rate of protein degradation occurred slowly during frozen storage, and the product is safe for consumption